Recensión: "La ciudad y sus miedos: la pasión restauradora" de Alicia Entel - Korstanje, Maximiliano (MAD, 2009)
Recensión del libro <!–[if gte mso 9]> Normal 0 21 false false false ES-TRAD X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>"La ciudad y sus miedos: la pasión restauradora" de Alicia Entel